Pengembangan Bahan Ajar Pada Sofware G-Suite For Education Untuk Meningkatkan Kemampuan Berfikir Kritis Siswa Kelas VIII - Zul Futria Wati; Yerizon Yerizon (University of Bengkulu, 2022)
The purpose of this study was to produce characteristics of mathematics teaching materials in the G-Suite For Education Software to improve critical thinking skills in valid, practical and effective grade VIII junior high school students. The teaching material developed is the Student Worksheet (LKPD) on the G-Suite For Education Software. This development research uses the Plomp development model which consists of 3 stages, namely preliminary research, development phase, and assessment phase. The subjects of this study were students of class VIII SMP El-Ma'arif Boarding School. The instruments used are validation sheets, student response questionnaires, and ability tests. The teaching materials developed are said to be valid if they meet content and construct validity. The instrument used is a validation sheet that contains aspects of presentation, feasibility of content and material, appearance and language. Validation was carried out by experts in mathematics education, educational technology, and Indonesian language. The practicality of teaching materials is seen from the participants' practicality questionnaire educate. The effectiveness of teaching materials is seen from the competence of students which consists of aspects of knowledge. The results of the validity data analysis indicate that the teaching materials in the G-Suite For Education Software produced have met the very valid criteria in terms of content and constructs. Teaching materials are practical in terms of implementation, convenience and processing time. Teaching materials have also been effective seen from student learning outcomes. Based on these results, it can be concluded that the teaching materials in the G-Suite For Education class VIII SMP that have been produced can be stated as valid, practical and effective.